DETERMINATION OF CHANGES IN HEMATOLOGICAL INDICATORS OF THE BLOOD OF COWS WITH ENDOMETRITIS - R. I. Bobomurodov; O. U. Kuldashev; S. Sh. Axmedov (Web of Journals Publishing, 2025)
This article examines the examination of blood samples taken from cows with endometritis, the levels of erythrocytes, leukocytes, monocytes, eosinophils, neutrophils in the blood, and biochemical parameters of blood serum, and provides practical conclusions.
Keywords: White blood cell count, erythrocyte, leukocyte, monocyte, eosinophil, neutrophil, acid, alkali, carotene, albumin, gammaglobulin, monocytopenia, resistance, phagocytosis.